Underveil throne armchair / Noor Atikah Hamdan - Hamdan, Noor Atikah (Universiti Teknologi MARA, Kedah, 2024)
The "Underveil Throne" is a revolutionary armchair that merges form and function for an exceptional seating experience, ideal for any veranda. Inspired by the features and character that are extracted from the veiled lady mushroom, it features a unique net-looking form that complements outdoor decor while providing ergonomic support. The design's structure resembles well-measured materials and components to ensure durability and elegance. Its sculptural design is visually appealing and provides ideal lumbar support, encouraging a comfortable sitting posture. Using sustainable materials, the "Underveil Throne" aligns with eco-conscious values, adding an environmentally friendly touch. This chair redefines modern seating by harmonising design and functionality